Järjestö jäänmurtajana : Suomen merimiesunioni työmarkkinaosapuolena ja suomalaisten laivatyöntekijöiden turvallisuuden vankentajana 1944-1980 - Soukola, Timo (Helsingin yliopisto, 2010)
Like an Icebreaker: The Finnish Seamen s Union as collective bargaining maverick and champion of sailors social safety 1944-1980. The Finnish Seamen's Union (FSU), which was established on a national basis in 1920, was one of the first Finnish trade unions to succeed in collective bargaining. In the early 1930s, the gains made in the late 1920s were lost, due to politically based internal rivalries, the Great Depression, and a disastrous strike. Unexpectedly the FSU survived and went on promoting the well-being of its members even during World War II. After the war the FSU was in an exceptionally favorable position to exploit the introduction of coordinated capitalism, which was based on social partnership between unions, employers and government. Torpedoes, mines and confiscations had caused severe losses to the Finnish merchant marine. Both ship-owners and government alike understood the crucial importance of using the remaining national shipping capacity effectively. The FSU could no longer be crushed, and so, in 1945, the union was allowed to turn all ocean-going Finnish ships into closed shops. The FSU also had another source of power. After the sailors of the Finnish icebreaker fleet also joined its ranks, the FSU could, in effect, block Finnish foreign trade in wintertime. From the late 1940s to the 1960s the union started and won numerous icebreaker strikes. Finnish seamen were thus granted special pension rights, reductions on income taxes and import duties, and other social privileges. The FSU could neither be controlled by union federations nor intimidated by employers or governments. The successful union and its tactically clever chairperson, Niilo Välläri, were continuously but erroneously accused of syndicalism. Välläri did not aim for socialism but wanted the Finnish seamen to get all the social benefits that capitalism could possibly offer. Välläri s policy was successfully followed by the FSU until the late 1980s when Finnish ship-owners were allowed to flag their vessels outside the national ...